PUBLIC VALUE OF JAYA TIRTA VILLAGE-OWNED ENTERPRISE (BUMDES) IN IMPROVING FARMERS’ WELFARE - Dini Artika Sukma; Oktarizka Reviandani (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the public value of BUMDes “Jaya Tirta” in improving community welfare in Gedongarum Village, Kanor District, Bojonegoro Regency. The study employs the public value theory proposed by Mark H. Moore, which is articulated through the Strategic Triangle framework consisting of three main elements: legitimacy and support, operational capacity, and substantive value. This research adopts a descriptive qualitative approach, with data collected through observation, interviews, and documentation involving seven informants. Data analysis was conducted using the interactive model of Miles and A Huberman. The findings indicate that BUMDes “Jaya Tirta” has successfully generated tangible public value for the community. From the dimension of legitimacy and support, the enterprise strengthens stakeholder confidence by ensuring openness in the delivery of accountability reports at Village Consultative Meetings, encouraging both formal and informal community involvement, and maintaining solid institutional arrangements based on Village Regulation No. 2 of 2017. In terms of operational capacity, BUMDes employs 57 personnel, manages an irrigation network covering more than 600 hectares of agricultural land, and generates revenues reaching approximately IDR 3.5 billion per planting season. Regarding substantive outcomes, the pump-based irrigation system significantly improves agricultural performance, raising crop yields from 6–7 tons to 10–12 tons per hectare and increasing planting intensity from a single harvest to two or even three harvests annually. The wider community also benefits indirectly through CSR allocations and contributions to Village Original Revenue (PAD). Despite these achievements, several challenges persist, including the need to enhance digital transparency, expand technical training for field workers, and reduce structural reliance on middlemen in grain distribution, which continues to limit the economic gains obtained by farmers.